Fish population dynamics in tropical waters a manual for use with programmable calculators - Pauly, Daniel (Manila, Philippines International Center for Living Aquatic Resources Management, 1984)
ICLARM Studies and Reveiws No. 8
Keywords: Fish populations--Tropics--Data processing--Handbooks, manuals, etc; Fish populations--Tropics--Mathematical models--Handbooks, manuals, etc